Nonlinear seismic response analysis of layered seabed considering seawater-seabed coupling effects - Fan, Hong-Fei; Wang, Yan-Zhen; Chen, Guo-Xing; Chen, Wei-Yun; Zhao, Kai; Zhu, Sheng-Dong (Frontiers in Marine Science, 2023)
Earthquake in the sea area is an important factor affecting the safety of marine engineering construction, seabed site seismic response analysis is an important preliminary work for marine engineering construction. Based on a fluid-solid weak coupling model which could simulate seawater-seabed interaction, four typical borehole sections along the proposed tunnel at Qiongzhou strait are selected to establish layered seabed models for studying the seabed site seismic responses affected by the seawater, seabed soft sediments and bedrock earthquake motion under bidirectional seismic excitation, in which the dynamic nonlinearity of the seabed soft soil is simulated by a generalized non-Masing constitutive model (DCZ model). The result shows: the suppression effect of seawater on seabed seismic motion exists only in the shallow range of seabed (< 50 m), and the suppression effect on the vertical seismic response is higher than that along the horizontal direction; the suppression effect of seawater on the seabed surface seismic motion and the frequency response phenomenon of “high frequency suppression, low frequency amplification” of seabed seismic response is positively correlated with seawater depth; The mean lines of the horizontal and vertical spectrum β obtained by numerical calculation are higher than the design spectrum in the land code within several period ranges, and the possibility of adverse effects induced by seawater and seabed soft sedimentation on the seismic resistance of marine engineering should be considered.